PROSPECTS OF TRANSFERRIG THE LARGE VOLUMES OF RADIO ASTRONOMY DATA - Isaev, E. A.; Tarasov, P. A. (Одеські астрономічні публікації, 2014)
Shows the volume of scientific data generated by the leading radio astronomical projects. The methods of transmission of large amounts of data in the present time and in the future are presented.